Antisthenes’ horse and Plato’s horseness: A metaphysical dispute between two Socratics - Silva, André Luiz Braga da (Revista Archai, 2025)
The paper analyzes some of the main testimonia concerning the relationship between Antisthenes of Athens and Plato. The testimonies on personal issues report hard tempers of both thinkers, a problematic relationship, and a (probably fictitious) moment of rupture between them. The testimonies on their philosophical controversy mainly report a deep quarrel concerning Platonic metaphysics. According to the sources, Antisthenes would have written an entire dialogue against the founder of the Academia, the Sathon, in which he ferociously criticized Plato by saying that the Ideas have no objective but only mental reality. After the explanation of the aspects of this criticism, the paper will assess whether it is possible to find in the Platonic corpus an answer to the other Socratic.